Revisiting the Parable of the Good Samaritan - Ryan, Maurice (Studies in Christian-Jewish relations, 2021)
The parable of the Good Samaritan (Luke 10:25-37) is among the best-known Gospel texts. It may also be one of the most mis-interpreted texts in the Gospels. The story of a traveler who comes to the aid of a victim of crime has inspired Christians for centuries to establish agencies to render assistance to those in need. The popular acclaim for the parable can cloud the meaning and significance of the story recounted in Luke’s Gospel. The ways the parable has been presented to and read by Christians represents a stumbling block in relations between Christians and Jews. This article surveys contemporary scholarly literature published for an English-speaking audience to determine what limitations and possibilities exist for understanding this parable. A close and careful reading of Luke’s text can reveal story elements that challenge traditional interpretations of this significant parable.